Shared Value Creation and Measurement Approaches Adopted by JSE Listed Companies - Wadesango, Ongayi (International Journal of Economics and Financial Issues, 2023)
Johannesburg Stock Exchange (JSE)-listed companies’ adoption of shared value is still in its infancy stage. In South Africa, some JSE-listed companies in the finance sector have adopted a shared value approach similar to responsible capitalism called Responsible Investments (RI) or impact investment. The purpose of the study was to investigate Shared Value Creation approaches adopted by JSE-listed companies. A documentary research approach, which consists of reviewing, analysing and examining information was adopted. The sources included journal articles, books, Frameworks, Guidelines and Codes. The results of the study indicated that JSE-listed companies, guided by the King Code, have adopted some elements of the shared-value model although integrated reports are purportedly not using the term.